Impact of Different Therapies on Haematological Parameters and Therapeutic Outcome in Subclinical Endometritic Buffaloes - Verma, Sanjeev Kumar; Kumar, Rajesh; Singh, Bhoopendra; Srivastava, Sushant; Verma, Rajesh Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of this study was to compare the effect of administration of intrauterine dextrose, s/c levamisol and intrauterine PGF2α on haematological indices and therapeutic response in endometritic buffaloes. Twenty eight repeat breeder buffaloes with subclinical endometritis were randomly assigned into four groups. Seven animals were kept as Control (untreated C), and the rests were assigned to three treatment group, i.e., T1 (Dextrose I/Ut, 50 mL 4 times on the day of estrus), T2 (Levamisol s/c, @ 2.5 mg/kg b.wt. on day 0, 7 and 14 of the cycle), and T3 (PGF2α I/Ut, @ 0.25 mg in 0.5 mL saline twice, on the day of first and next estrus). Following treatment the values of Hb, TEC and PCV elevated significantly and TLC values dropped to normal or near normal in all three treatment groups as compared to control group. Furthermore, the post-treatment neutrophils and lymphocytes counts were elevated significantly in all four groups. However, there was no any definite pattern of eosinophils and basophils. The therapeutic response (clinical recovery) was 14.29, 71.43, 85.71 and 42.86 % in T0, T1, T2 and T3 group, respectively. The corresponding conception rates were 0.00, 60.00, 66.67 and 66.67 %. The results conclude that, Dextrose intrauterine, Levamisol s/c, and PGF2α intrauterine can be used effectively to manage subclinical endometrtitis in buffaloes.